Jak se dělá rasová válka? Kritická diskursivní analýza neonacistických textů - Jan Šamánek (AntropoWebzin, 2010)
This article is a critical discourse analysis of set of texts published by one of leading Czech neo-nazi internet servers. The author embracing the standpoint of radical democracy shows discoursive sequentiality of analyzed texts and development of the neo-nazi discourse according to events that took place before, during, between and after three major neo-nazi demonstrations in Janov and Přerov, Czech Republic in years 2008 and 2009. It is shown that the discourse uses the occurrence of local inhabitants of Janov and Přerov on demonstrations for construction of reality of a starting racial war and for legitimization of demonstrators’ violence against Roma inhabitants and police. The racist ideological basis of the discourse is also shown. The article explains how both successes and failures of all demonstrations are used as motivating discoursive tools for mobilization and propagation for following events and how does the discourse react to them.